Substantiation of technical characteristics of promising high-speed multi-band broadband military radio stations - Symonenko, Oleksandr (Technology audit and production reserves, 2022)
The issue of improving the technical characteristics of promising high-speed multi-band broadband military radios is an important issue. It happens because of the increase in the number of devices of communication in information and telecommunication networks, as well as the growing requirements for the level of technical characteristics of these devices. Given the above, the object of the research is a promising high-speed multi-band broadband military radios. The subject of the research is the technical characteristics of promising high-speed multi-band broadband military radios. In the course of the research, classical methods of analysis and synthesis were used. The research analyzes global trends in the construction and development of wireless access networks, which allows concluding on the prospects of development (purchase) and implementation of high-speed multi-band broadband military radios for the Armed Forces of Ukraine. The results of the analysis of characteristics and parameters of high-speed multi-band broadband radio stations of the world’s leading countries allow to determine the main features and requirements for promising radios, as well as to substantiate the use of high-speed radio stations in the Armed Forces of Ukraine. The conditions and factors influencing the possibilities of using promising broadband radio stations in the conditions of modern wars and armed conflicts are determined. The analysis allows to conclude that broadband radio access systems will be used to organize access to information resources in the information and telecommunications environments of network-centric and information wars.